Vers une ontologie de domaine pour l’analyse des tissus anciens. Le projet Silknow et le cas du patrimoine soyeux européen - Marie Puren; Pierre Vernus (Humanités Numériques)
In this article, we present the Silknow project (Silk heritage in the knowledge society: from punched card to big data, deep learning and visual/tangible simulations, 2018-2021). This project aimed to use Semantic Web technologies to give greater visibility to silk objects produced and consumed in Europe between the 15th and 19th centuries. Silk is a particularly important material in European history, and it has been used to produce exceptional objects of great historical interest. However, it is a threatened heritage that is little known to the general public. We present the methodology used to develop a knowledge graph, and in particular the steps that were necessary to create the underlying data model, based on the CIDOC-CRM or CIDOC Conceptual Reference Model. We also propose a CIDOC-CRM-compatible model to express the complex semantics of the creation and production process of ancient silk fabrics.